Succession of a natural desert vegetation community after long-term fencing at the edge of a desert oasis in northwest China - Zhang, Yan; Wang, Guohua; Gou, Qianqian; Zhang, Yu; Liu, Jing; Gao, Min (Frontiers in Plant Science, 2023)
Fencing is the most economical method of restoring degraded desert ecosystems, and plays an important role in promoting plant community diversity and productivity, as well as stable ecosystem structure and function. In this study, we selected a typical degraded desert plant community (Reaumuria songorica–Nitraria tangutorum) on the edge of a desert oasis in the Hexi Corridor in northwest China. We then investigated succession in this plant community and corresponding changes in soil physical and chemical characteristics over 10 years of fencing restoration to analyze the mutual feedback mechanisms. The results showed that: 1) The diversity of plant species in the community increased significantly over the study period, especially the number of herbaceous layer species, which increased from four in the early stage to seven in the late stage. The dominant species also changed, with the dominant shrub layer species shifting from N. sphaerocarpa in the early stage to R. songarica in the late stage. The dominant herbaceous layer species changed from the annual herb Suaeda glauca in the early stage to S. glauca and Artemisia scoparia in the middle stage, and ultimately to A. scoparia and Halogeton arachnoideus in the late stage. In the late stage, Zygophyllum mucronatum, H. arachnoideus, and Eragrostis minor began to invade, and the density of perennial herbs also increased significantly (from 0.01 m-2 to 0.17 m-2 for Z. kansuense in year seven). 2) As the duration of fencing increased, the soil organic matter (SOM) and total nitrogen (TN) contents first decreased then increased, whereas the available nitrogen, potassium, and phosphorus contents showed the opposite trend. 3) Changes in community diversity were mainly affected by the nursing effects of the shrub layer, as well as soil physical and chemical properties. That is, fencing significantly increased the vegetation density of the shrub layer, which promoted growth and development of the herbaceous layer. However, community species diversity was positively correlated with SOM and TN. The diversity of the shrub layer was positively correlated with the water content of deep soil, whereas that of the herbaceous layer was positively correlated with SOM, TN, and soil pH. The SOM content in the later stage of fencing was 1.1 times that in the early stage of fencing. Thus, fencing restored the density of the dominant shrub species and significantly increased species diversity, especially in the herb layer. Studying plant community succession and soil environmental factors under long-term fencing restoration is highly significant for understanding community vegetation restoration and ecological environment reconstruction at the edge of desert oases.